THE ROLE OF LIPOTROPIC THERAPY IN PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE BEFORE AND AFTER CORONARY REVASCULARIZATION - R. N. Adzhiev; M. S. Safarova; M. V. Ezhov (Рациональная фармакотерапия в кардиологии, 2015)
Review of large of trials that prove the positive impact of high-dose lipid-lowering therapy on the prognosis in patients with ischemic heart disease (IHD) are presented. The data on the efficacy of the lipid profile correction by lipid apheresis in patients with hypercholesterolemia that is refractory to optimal medical therapy are showed. The results of the large trials (LIPS, ARMYDA, NAPLES II, ARMYDA-RECAPTURE, Post-CABG, TNT) and meta-analyzes on the role of statins, prescribed before and after coronary artery bypass surgery and stenting, in reducing the risk of early and late cardiac events and the need for repeat myocardial revascularization are analyzed. The issue of therapeutic apheresis should be considered in cases of refractory hypercholesterolemia according to ESC/EAS Guidelines for the management of dyslipidaemias (2011). The tendency to reduction in the risk of stent restenosis and vein graft lesions after lipid apheresis is found in very high risk patients with IHD and refractory hypercholesterolemia that underwent coronary stenting or bypass surgery.